GOLDEN RATIO INTERPRETATION ON 150 FLOWERS: THE BASIC INFORMATION TO DEVELOP ECOTOURISM IN BOGOR, INDONESIA - Mutiara, Muhammad Moldynniz; Avenzora, Ricky; Arief, Harnios (Indonesian Journal of Forestry Research, 2024)
The Aesthetic value is one of the factors in order to attract tourists to visit. Flowers are one form of tourist attraction that symbolizes beauty, flowers can be used as an object of interpretation for the development of ecotourism, especially in interpreting the meaning of the aesthetic value. Assessment of beauty can be measured by a number that is believed to have beauty, namely by using the golden ratio. Research has shown that the golden ratio actually exists in flowers. The knowledge of the golden ratio of flowers, in addition to increasing tourist attraction, can also be used as an interpretation for tourists because the aesthetic value is very important to the human relationship with nature, and the motivation to protect it. Golden ratio analysis was performed on 150 flowers. A flower is said to have a golden ratio if the ratio results in a comparison of flower morphology producing a number of 1.618 or close to that number. The discovery of the golden ratio in all flowers shows that flowers are creations that have aesthetic value so visitors are expected to be able to interpret the importance of the value of beauty in living things for their tour experience